Population prevalence and correlates of prolonged and shortened QTc intervals in a nationwide survey of adults in China: a report from Chinese arrhythmia epidemiology cross-sectional study - Tan, Li-Guo; Liu, Jing-Xuan; Guo, Fei; Lin, Jing; Xiong, Ran; Fu, Hao; You, Hao-Ming; He, Liu; Xia, Shi-Jun; Du, Xin; Dong, Jian-Zeng (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveQT interval irregularities correlate with severe arrhythmias and sudden cardiac death. However, epidemiological data on QT intervals in Chinese adults are lacking. This study aimed to elucidate the distribution of the QT interval (QTc) patterns in Chinese adults and the risk factors associated with a prolonged QTc interval and shortened QTc interval.MethodsThis study was based on data from the Chinese Arrhythmia Epidemiology Cross-Sectional Study conducted in seven provinces of China between 2014 and 2016. A total of 42,031 Chinese adults (age ≥ 45 years) were included in the study, and body surface electrocardiograph (ECG) QTc and other indices were systematically analyzed retrospectively among the participants.ResultsThe mean QTc interval in Chinese adults was 429.4 ± 25.1 ms (men: 429.7 ± 25.2 ms; women: 430.0 ± 22.0 ms; P = 0.97). The 2.5th and 97.5th percentile QTc intervals were 384 and 480 ms, respectively. The prevalence of a long QTc interval (QTc > 440 ms) and a very long QTc interval (QTc > 500 ms) in Chinese adults was 32.64% and 0.60%, respectively. Multifactorial logistic regression analysis found that Han Chinese ethnicity, rural residence, hypertension and health insurance were independently associated with an increased risk of long QTc intervals (all P < 0.05). The prevalence of short QT intervals was 4.87% (American Heart Association criteria), 1.84% (European Society of Cardiology criteria), and 0.02% (heart rhythm criteria). Individuals with QTc < 320 ms were not observed in this study. Abnormal renal function (eGFR (estimated glomerular filtration rate) <90 ml/min/m2) was independently linked to an elevated risk of short QTc intervals; hypertension was strongly associated with reduced short QTc intervals.ConclusionThis study provides epidemiological data on the distribution of QT intervals in Chinese adults. Range of the normal QTc interval in Chinese adults is 384–480 ms. The QTc interval is longer in Chinese adults of Han Chinese ethnicity than in those of non-Han Chinese ethnicity. Hypertension is closely associated with a long and short QTc interva, which should be considered when administering medications to hypertensive patients in clinical practice. No individuals with a QTc interval ≤320 ms were observed in this study, indicating that short QT syndrome may be very rare in the Chinese adult population.